Conserved nodulation genes from the non-legume symbiont Bradyrhizobium sp. (Parasponia). - Scott, K F (1986)
A nodulation locus from the broad-host-range, non-legume symbiont Bradyrhizobium sp. (Parasponia) strain ANU289, has been identified by hybridisation to cloned Rhizobium trifolii nodulation (nod) genes. Transfer of cloned ANU289 nod genes to R.trifolii nodulation-deficient mutants showed that the locus contains a functional homologue of the R. trifolii nodD gene. DNA sequence analysis revealed the presence of three additional genes nodA, nodB and nodC clustered adjacent to nodD. The four genes from ANU289 share substantial sequence homology with those characterised from narrow-host-range Rhizobium strains. A novel 700-bp sequence inserted between the nodD and nodABC genes encodes an open reading frame designated nodK and is oriented in the same direction as nodABC. nodKABC appear to be organized in a single transcriptional unit and nodD is oriented divergently to nodKABC. A 35-bp sequence containing the ribosome binding site for the nodD gene and an AT-rich core sequence has been identified by comparison with sequences from other Rhizobium strains and is likely to be implicated in the plant-mediated induction of nodulation gene expression.